A Room with a View — A Valuation of the Mediterranean Sea View - Aliza Fleischer (European Regional Science Association (ERSA), 2012)
Aesthetic view is one of the ecosystem services of the Mediterranean Sea which can be estimated using price differences in the hotel market. Hotels situated on the Mediterranean Sea charge higher prices for a room with a sea view than for a room without it. The value of this view in 10 major Mediterranean regions was estimated in this paper using a hedonic price method. Data on 2,819 hotel rooms in high season and 2,406 rooms in the low season were collected from Booking.com and fixed effects regression was used to estimate the model coefficients. Hotel room prices were found to be higher by about 10% for a room with a view than for one with no view specification. No significant difference was found between regions or season. These findings lend support to the fact that the view of the Mediterranean is equally valued in all regions.
Keywords: Q51; 330; Sea view; Mediterranean; Hedonic prices; Fixed effects regression